KARAKTERISTIK RESPONDEN DALAM MENGISI KUESIONER TENTANG HAMBATAN PENGGUNAAN E-LEARNING - Nurmiati, Siti; Rusli, Rusli (JURNAL REKAYASA INFORMASI, 2025)
This study aims to identify the characteristics of respondents who have participated in answering the questionnaire about the barriers to the use of e-learning in Higher Education, located in the Bekasi area, West Java. After the data was collected, processed and analyzed using SPSS ver 29 software, it can be seen that the characteristics of respondents who participated in answering the questionnaire about the barriers to the use of e-learning can be grouped into several (can be seen in Figure 2 - Figure 13) namely Age characteristics ranging from 18-24 years as many as 265 (76.8%), Male Gender characteristics as many as 191 (55.4%), Bachelor's Education characteristics as many as 345 (100%), Information Systems Study Program characteristics as many as 250 (72.5%), Device characteristics used Laptops and Smartphones as many as 248 (71.9%), Daily Frequency of Use characteristics as many as 306 (88.7%), Year of Using Devices 1-3 years as many as 109 (31.6%), Internet Access Place characteristics Home, Campus and Public Places as many as 166 (48.1%). Characteristics of Internet Usage Years more than 8 years as many as 190 (55.1%), characteristics of e-learning Platform used, namely Custom e-learning as many as 175 (50.7%), characteristics of Daily Frequency of Use of e-learning as many as 172 (49.9%), characteristics of Years Using E-learning 1-3 years as many as 208 (60.3%). While the results of significant testing between two variables, namely Study Programs with Internet Access Places with p-value = 0.026 is smaller than 0.05 so that there is a significant relationship between the two variables tested (can be seen in Figure 18).